Experiences of heads of department in managing teaching and learning in commercial subjects: A literature-based study - Ayanda Maseko (International Journal of Studies in Inclusive Education)
Heads Of Department (HODs) in schools have raised concerns over teacher absenteeism, tardiness, and workload. HODs are situated in the School Management team's middle management and are essential in ensuring that teaching and learning occur. To carry out this task, they must efficiently manage their time. HODs, on the other hand, face difficulties in their roles. However, this study investigated the experiences of HODs in managing commercial teaching and learning. Qualitative techniques were used in this study to better understand the roles of HODs in controlling teaching and learning on commercial topics. It adopted a desktop research design and was literature-based. The information was gleaned from published journal articles, textbooks, and document analysis. Ten books, articles, and journals were selected as the foundation for literature assessment. The study's findings showed the roles that HODs in commercial subjects follow to support them as they carry out their duties, challenges faced by HODs in managing commercial subjects, and strategies that assist the HODs to carry on with their duties regardless of the challenges they face. This study suggested that HODs must encourage teachers to attend topic workshops, and that continuous professional development is required. Teachers should devour widely, research their areas of expertise, and conduct themselves professionally. Present, timely, and actively involved in extensive course planning, preparation, and delivery. HODs are welcome to visit classrooms anytime to ensure effective teaching and learning occur at departmental or subject meetings.